How to write a term paper - James, Elizabeth; Barkin, Carol (New York : Lothrop, Lee & Shepard Books, 1980)
Presents advice on how to select a topic, plan one's time, do research, organize notes, make an outline, and write an original term paper including footnotes.
Includes index.
Bibliography: p. 90.
Keywords: Academic writing -- Juvenile literature; Research -- Juvenile literature; Report writing; Research